Bridging Legal, Religious, and Human Rights Perspectives on LGBT Issue - Nurnisaa AS; Okta Y, Setyo Luthfi (International Journal of Humanities, Law, and Politics, 2024)
This study examines the legal, religious, and human rights views of the LGBT community in Indonesia. This study aims to provide a broader understanding of how society's views of LGBT are influenced by legal, religious, and human rights factors. The formulation of the problem in this study focuses on how the legal, Islamic religion, and human rights views of the LGBT community in Indonesia. This study uses a qualitative approach with literature study as the main method, focusing on the analysis of relevant written sources, such as books, articles, reports, laws, interpretations, hadiths, and human rights documents. Despite legal efforts through the Constitutional Court's decision rejecting the criminalization of same-sex activity, discrimination against LGBT individuals continues, both through regional regulations and conservative religious views. The Islamic perspective that views homosexuality as deviant behavior exacerbates social stigma and legal challenges for LGBT individuals.